Ergebnisse des deutschen Schulter- und Ellenbogenprothesenregisters (SEPR): Anatomische oder inverse Prothese bei B2-Glenoid? = Results from the German shoulder- and elbow arthroplasty register (SEPR) : anatomic or reverse shoulder arthroplasty in B2-glenoids? - Magosch, Petra; Zeifang, Felix (Der Orthopäde, 2017)
BackgroundAnatomic shoulder arthroplasty in osteoarthritis with biconcave glenoid wear results in decreased functional results and a higher rate of early glenoid loosening.AimThe aim of the data analysis of the German shoulder arthroplasty register was to clarify whether reverse shoulder arthroplasty can provide better functional results and a lower complication rate than anatomic arthroplasty in osteoarthritis with biconcave glenoid wear.MethodsThe analysis included 1052 completely documented primary implanted arthroplasties with a minimum follow-up of 2 years. In 119 cases, a B2-type glenoid was present. Out of these cases, 86 were treated with an anatomic shoulder arthroplasty, and in 33 cases a reverse shoulder arthroplasty was implanted. The mean follow-up was 47.6 months.ResultsThe Constant score with its subcategories, as well as the active range of movement improved significantly after anatomic and after reverse shoulder arthroplasty.DiscussionWe observed no difference in functional results between both types of arthroplasty; however, reverse arthroplasty showed a significant higher revision rate (21.2%) (3% glenoid loosening, 6% prosthetic instability) than anatomic shoulder arthroplasty (12.8%) (11.6% glenoid loosening, 1.2% prosthetic instability), whereas anatomic shoulder arthroplasty showed a higher rate of glenoid loosening. Functional and radiographic results of both types of arthroplasty are comparable with the results reported in the literature, although our analysis represents results from an implant registry (data pertaining to medical care quality).